Non-Tariff Measures, Import Competition, and Exports - Cali, Massimiliano; Montfaucon, Angella Faith (World Bank, Washington, DC, 2021)
The empirical evidence on the impact of import competition on economic performance relies mainly on import tariff liberalization as the source of changes to competition. This paper extends this evidence by focusing on non-tariff measures, an increasingly important trade policy tool globally. The analysis examines the competition effect of four specific non-tariff measures on the exporting activity of the universe of Indonesian firms. The focus is on measures that do not clearly address any negative externalities of imports—the supposed objective of non-tariff measures—and hence appear to be protectionist in nature. The results suggest that by restricting import competition, these measures reduce the survival of firms in export markets as well as the intensive and extensive margins of their exports. Non-tariff measures have a more negative effect than import tariffs in most cases and these results are robust to various checks. The analysis provides suggestive evidence that markups are an important channel through which these effects are mediated.